Dilemas da democracia: a representação política nos novos espaços de participação - de Moura, Joana Tereza Vaz (2015)
The main objective of this article is to discuss the deadlocks that appear when new spaces of representation are open, as for the case of several Councils, that is, to understand the presence of civil society in alternative forms of participation and political representation. In the last instance, it seeks to understand how representation and participation can survive together with democracy. To work with these issues, I take some authors which have helped to think about that new form of participation and political representation, emphasizing, among others aspects, the process of reconfiguration of the representation in which social actors build political representativeness through others means than the electoral ones. It is intended, in this way, to contribute to the understanding and development of democratic practices in Brazil.